Misattributions and misnomers in mechanics: Why they matter in the search for insight and precision of thought - Reddy, J. N.; Srinivasa, Arun R. (Vietnam Journal of Mechanics, 2020)
The purpose of this article is to bring some examples of misattributes (i.e., theories and models that bear some one’s name while the idea belongs to someone else) and misnomers (i.e., words or phrases that are either incorrect or inaccurate) to the attention of the colleagues in the field, and correct them so that these incorrect phrases and attributions and misnomers are not repeated in the future writings. In the process, we also discuss the purpose of a literature reviews and the need for precision of thought in naming ideas or concepts.  It is hoped that people will be careful and precise in using the words, names, and phrases correctly (since after all, these represent ideas that need to be communicated) and not propagate inaccurate information in the literature. The discussion presented is restricted to mostly structural and computational mechanics.